# Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises - Page 242: 33

m=18

#### Work Step by Step

Simplifying 9m + -3(m + -5) = 7m + -3 Reorder the terms: 9m + -3(-5 + m) = 7m + -3 9m + (-5 * -3 + m * -3) = 7m + -3 9m + (15 + -3m) = 7m + -3 Reorder the terms: 15 + 9m + -3m = 7m + -3 Combine like terms: 9m + -3m = 6m 15 + 6m = 7m + -3 Reorder the terms: 15 + 6m = -3 + 7m Solving 15 + 6m = -3 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. 15 + 6m + -7m = -3 + 7m + -7m Combine like terms: 6m + -7m = -1m 15 + -1m = -3 + 7m + -7m Combine like terms: 7m + -7m = 0 15 + -1m = -3 + 0 15 + -1m = -3 Add '-15' to each side of the equation. 15 + -15 + -1m = -3 + -15 Combine like terms: 15 + -15 = 0 0 + -1m = -3 + -15 -1m = -3 + -15 Combine like terms: -3 + -15 = -18 -1m = -18 Divide each side by '-1'. m = 18 Simplifying m = 18

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.